Amifostine Suppresses the Side Effects of Radiation on BMSCs by Promoting Cell Proliferation and Reducing ROS Production - Bo Huang; Tao He; Qianqian Yao; Liang Zhang; Yang Yao; Hua Tang; Ping Gong (Stem Cells International)
This study is aimed at investigating the effect of amifostine (AMI) on rat bone marrow stromal stem cells (BMSCs) exposed to 2 Gy radiation. The BMSCs were divided into four groups, namely, group A that received 0 Gy radiation, group B that received 0 Gy radiation and AMI, group C that received 2 Gy radiation, and group D that received 2 Gy radiation and AMI. The proliferation, apoptosis, and distribution of BMSCs in the cell cycle, along with their osteogenesis ability, adipogenesis ability, and ROS production, were subsequently examined. The levels of ALP, PPARγ, P53, and TNFα were determined by Western blotting. The results demonstrated that the proliferation of BMSCs and the levels of ALP in group C were much lower than those in group A. The production of ROS and levels of PPARγ, P53, and TNFα in the group that received 2 Gy radiation were much higher than those in group A. Furthermore, the production of ROS and the levels of PPARγ, P53, and TNFα were much lower in group D than in group C. Additionally, the levels of ALP and extent of cell proliferation were much higher in group D than in group C. The results demonstrated the potential of AMI in reducing the side effects of radiation in BMSCs and in treatment of bone diseases caused by radiation.